2000
DOI: 10.1016/s0167-9317(00)00312-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of MOS-integrated metallic single electron memories

Abstract: The fabrication of a lateral single electron memory (LSEM) based on the integration of a metallic multiple tunnel junction (MTJ) and a memory node (MN) on a Si metal oxide semiconductor field effect transistor (MOS) has been investigated. High resolution electron beam lithography (HREBL) was used to fabricate devices presenting good morphological characteristics. The MN can be made as narrow as 50 nm, with an MTJ comprising a 5x5 array of sub-5 nm Au islands deposited by thermal evaporation, and implemented on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The NDR peak is commonly observed in nanocrystals embedded dielectrics (14,15,17). The NDR peak is not detected at the high temperature because it is difficult to retain the high energy electrons (19,20). Previously, it was reported that the leakage current of the control sample, i.e., with the ZrHfO high-k gate dielectric without any embedded layers, followed two different mechanisms in the negative V g region, i.e., Schottky emission (SE) at the low electric field and Poole-Frenkel (P-F) mechanism at the high electric field (21).…”
Section: Resultsmentioning
confidence: 99%
“…The NDR peak is commonly observed in nanocrystals embedded dielectrics (14,15,17). The NDR peak is not detected at the high temperature because it is difficult to retain the high energy electrons (19,20). Previously, it was reported that the leakage current of the control sample, i.e., with the ZrHfO high-k gate dielectric without any embedded layers, followed two different mechanisms in the negative V g region, i.e., Schottky emission (SE) at the low electric field and Poole-Frenkel (P-F) mechanism at the high electric field (21).…”
Section: Resultsmentioning
confidence: 99%